Percutaneous Electrical Nerve Stimulation (PENS) as a Rehabilitation Approach for Reducing Mixed Chronic Pain in Patients with Musculoskeletal Disorders - Alessandro de Sire; Antonio Ammendolia; Lorenzo Lippi; Giacomo Farì; Carlo Cisari; Marco Invernizzi (Applied Sciences, 2021)
“Mixed pain” is a term recently introduced to define the overlapping of nociceptive, neuropathic and nociplastic pain. To date, it has been reported that pharmacological treatments might have a modest effectiveness on patients affected by mixed chronic pain, with detrimental consequences in terms of disability, physical function and health-related quality of life. In this scenario, Percutaneous Electrical Nerve Stimulation (PENS), a mini-invasive neuromodulation technique, has been recently suggested as a promising approach for the complex management of mixed pain in musculoskeletal disorders. Albeit PENS showed to be effective in reducing unspecified pain in several chronic pain conditions, there is still a lack of evidence in the literature about its role in the management of neuropathic or mixed pain not responsive to pharmacological treatments. Therefore, by the present scoping review, we portray the potential effects of PENS in the multidisciplinary and multidimensional management of mixed chronic pain in patients with musculoskeletal disorders.